Hurricane Generated Seas. - Ochi, Michel K. (Elsevier, 2003)
Hurricanes are one of the most adverse aspects of the ocean environment, with the potential to cause a disastrous event for marine systems in the ocean. This is an invaluable reference for all involved in the field of naval, ocean and coastal engineering. The work clarifies hurricane generated sea conditions necessary for the design and operation of marine systems in a seaway, and provides information for the protection of near shore / onshore structures and the environment at the time of hurricane landing.
Keywords: Hurricanes.; Ocean waves.; elektronické knihy; electronic books